2004
DOI: 10.1186/1471-230x-4-22
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin A and cyclin D1 as significant prognostic markers in colorectal cancer patients

Abstract: Background: Colorectal cancer is a common cancer all over the world. Aberrations in the cell cycle checkpoints have been shown to be of prognostic significance in colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
134
3
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(153 citation statements)
references
References 22 publications
9
134
3
1
Order By: Relevance
“…19 Handa et al showed cyclin A overexpression to be associated with poor outcome and to be an independent prognostic factor in colorectal cancer. 20 Bahnassy et al 21 and Nozoe et al 22 have reported similar results concerning colon cancer. In contrast, Li et al showed that cyclin A expression gradually increases in the colon adenoma-carcinoma sequence, but patients with high cyclin A immunoreactivity had better survival than those with reduced cyclin A expression.…”
Section: Discussionsupporting
confidence: 70%
“…19 Handa et al showed cyclin A overexpression to be associated with poor outcome and to be an independent prognostic factor in colorectal cancer. 20 Bahnassy et al 21 and Nozoe et al 22 have reported similar results concerning colon cancer. In contrast, Li et al showed that cyclin A expression gradually increases in the colon adenoma-carcinoma sequence, but patients with high cyclin A immunoreactivity had better survival than those with reduced cyclin A expression.…”
Section: Discussionsupporting
confidence: 70%
“…7 Several studies have provided evidence that several molecular markers may be useful in defining the risk for individual patients with CRC after surgery and in identifying patients who may benefit most from adjuvant chemotherapy. 24,31,32 We investigated the possible prognostic and predictive values of c-Kit, COX2, p53, and K-ras in patients with stage II CRC. A novel and interesting finding in the current study is the high frequency of c-Kit overexpression in stage II CRC patients (59.3%) compared with what was reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, upregulation of these genes may contribute to growth inhibition in ATRA-treated Wilms tumor cells. CCNA2 and CKS2 are well-known cell cycle checkpoint genes whose overexpression was linked to cell proliferation and tumor progression (Urbanowicz-Kachnowicz et al, 1999;Bahnassy et al, 2004). Hence, downregulation of these genes in Wilms tumors may convey antiproliferative effects.…”
Section: Genes Involved In Cell Proliferation and Matrix Remodelingmentioning
confidence: 99%